THE ROLE OF ENTERPRISE RISK MANAGEMENT ON ORGANIZATIONAL RESILIENCE IN THE ERA OF DIGITAL TRANSFORMATION: A CASE STUDY OF PT UNILEVER INDONESIA TBK (POLITEKNIK LP3I JAKARTA, 2026)
Digital transformation has changed the way organizations conduct operations, make strategic decisions, and create business value. On the other hand, digital transformation has also increased the complexity of risks faced by companies, such as cyber risks, operational disruptions, changes in consumer behavior, and uncertain business environments. In facing these challenges, Enterprise Risk Management (ERM) is a crucial approach to ensure organizations are able to identify, manage, and respond to risks in an integrated manner. This study aims to analyze the role of Enterprise Risk Management on organizational resilience in the era of digital transformation using a case study of PT Unilever Indonesia Tbk. This research employed a qualitative approach with a case study method through document analysis of the annual report, sustainability report, and corporate governance report of PT Unilever Indonesia Tbk for the 2020–2024 period. The analysis was conducted based on the five components of the 2017 COSO Enterprise Risk Management Framework: Governance and Culture, Strategy and Objective Setting, Performance, Review and Revision, and Information, Communication, and Reporting. The results indicate that ERM implementation plays a role in strengthening organizational resilience by improving risk identification capabilities, improving adaptive decision-making, strengthening governance, and enhancing organizational capacity to address business change and disruption. Furthermore, the integration of risk management with corporate strategy supports operational continuity and the achievement of organizational goals amidst the dynamics of digital transformation. This research provides theoretical contributions to the development of Enterprise Risk Management and organizational resilience studies, as well as practical implications for companies striving to build more resilient and sustainable organizations in the digital era.